1978
DOI: 10.1161/01.res.42.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial dysfunction and hemodynamic abnormalities during strenuous exercise in dogs with limited coronary flow.

Abstract: SUMMARY We studied regional myocardial dynamics during brief, strenuous bouts of running in 12 conscious dogs by telemetry before and after partial circumflex coronary artery (CCA) constriction. Regional myocardial dimensions were measured by an ultrasonic method in a control segment (CS) and segment to be made ischemic (IS). In control runs heart rate (HR), left ventricular (LV) systolic pressure, and dP/dt increased markedly, and segment end-diastolic lengths (EDL) increased along with augmentation of region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Investigations in conscious experimental animals with chronic coronary arterial stenosis indicated that exercise causes severe regional myocardial dysfunction and hemodynamic abnormalities. 22 Drug-induced changes in regional left ventricular function have also been studied in experimental formation is available on comparative effects of these agents on regional left ventricular function in man. With the introduction of noninvasive radionuclide ventriculography and quantitative analysis of regional left ventricular function, differences of drug effects on normal, ischemic and scar myocardial segments can be studied in man.…”
mentioning
confidence: 99%
“…Investigations in conscious experimental animals with chronic coronary arterial stenosis indicated that exercise causes severe regional myocardial dysfunction and hemodynamic abnormalities. 22 Drug-induced changes in regional left ventricular function have also been studied in experimental formation is available on comparative effects of these agents on regional left ventricular function in man. With the introduction of noninvasive radionuclide ventriculography and quantitative analysis of regional left ventricular function, differences of drug effects on normal, ischemic and scar myocardial segments can be studied in man.…”
mentioning
confidence: 99%
“…The change in subendocardial flow in St-Ex I was also not The modest abnormalities in regional contractile function observed in this study during exercise would undoubtedly be difficult to detect by conventional echocardiographic or nuclear angiographic analysis of regional wall motion. 6 However, recent studies using two-dimensional echocardiography with hyperemia at rest produced by dipyridamole readily demonstrated induced regional contraction abnormalities in patients with coronary stenoses of 70% or greater. 37 Newer techniques such as tomographic gated blood pool radionuclide ventriculography,38 nuclear magnetic resonance imaging,39 or digital processing of intravenous ventricular fluorographic images40 during exercise or hyperemia eventually may allow reliable detection of such minor contraction abnormalities in patients with subcritical coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…3, 596-605, 1986. EXERCISE-INDUCED ischemia has been studied in detail experimentally with analyses of regional myocardial blood flow (MBF),'-s regional contraction, [4][5][6][7] and overall left ventricular function.5 [8][9] These data and other studies in resting conscious dogs'0-2 have established that regional contractile function is responsive to reductions in MBF, especially to the subendocardium. For example, in the presence of critical coronary stenosis (normal resting flow but lack of vasodilator reserve), subendocardial coronary flow drops 50% below the resting value during exercise, with an assoicated 70% decrease of systolic wall thickening below the resting value.…”
mentioning
confidence: 99%
“…Since a functional antagonism to coronary vasodilatation by intravenous administration of DHE was shown in a previous study (Raberger et al, 1976) (Battler et al, 1980;Brugge-Asperheim et al, 1969;Gallagher et al, 1982;Tomoike et al, 1978). The segment length was normalized according to Theroux et al (1976).…”
Section: Introductionmentioning
confidence: 99%